Afroindoamérica: A critical re-reading of its methodological itineraries in the Caribbean - Pacheco Valera, Irina (Comparative Cultural Studies: European and Latin American Perspectives, 2025)
This article presents the main epistemological, theoretical-methodological schools or currents for addressing social studies on Afroindoamerica. With an interdisciplinary and holistic approach, it seeks contours of interaction between various disciplines of social knowledge, framed within epistemological discussions. These references have significant implications for scientific research as they foster new analytical approaches that refunctionalize theoretical-methodological discourse and its appropriate historical contextualization. Thus, this research provides new perspectives for approaching Afroindoamerica with a multidimensional view, relativizing the essentialist and binary tradition of western thought, and offering a reflective proposal on social processes with a critical and decolonizing mindset. Moreover, it examines how these methodological currents influence the understanding of identity and cultural resistance in afro-indigenous contexts.